Implications In Handing Gross Human Rights Violations In Paniai District - Sri Iin Hartini; Eren Arif Budiman (Jurnal Ilmiah Dunia Hukum, 2023)
The aim of this research is to evaluate the function of Komnas HAM in handling cases of human rights violations in Paniai Regency, as well as obstacles to handling human rights cases in Paniai Regency. This research uses empirical juridical research methods, namely methods or procedures used to answer research problems by first examining secondary data and then examining primary data in the field. The aim of the research is to collect field data through interview techniques and respond to the author's concerns regarding the handling of human rights violations in Paniai Regency, namely cases of shootings against civilians by armed officers from the TNI. Based on research findings, the difficulties faced by the Papua Province Representative Commission for National Human Rights in resolving cases of serious human rights violations in Paniai Regency are in terms of examining witnesses and victims who continue to be rejected, due to the lack of public trust. in law enforcement. Therefore, Komnas HAM needs to foster a sense of public trust.